Waste Materials from Tetra Pak Packages as Reinforcement of Polymer Concrete - Miguel Martínez-López; Gonzalo Martínez-Barrera; Carlos Barrera-Díaz; Fernando Ureña-Núñez; Witold Brostow (International Journal of Polymer Science)
Different concentrations (from 1 to 6 wt%) and sizes (0.85, 1.40, and 2.36 mm) of waste Tetra Pak particles replaced partially silica sand in polymer concrete. As is well known, Tetra Pak packages are made up of three raw materials: cellulose (75%), low density polyethylene (20%), and aluminum (5%). The polymer concrete specimens were elaborated with unsaturated polyester resin (20%) and silica sand (80%) and irradiated by using gamma rays at 100 and 200 kGy. The obtained results have shown that compressive and flexural strength and modulus of elasticity decrease gradually, when either Tetra Pak particle concentration or particle size is increased, as regularly occurs in composite materials. Nevertheless, improvements of 14% on both compressive strength and flexural strength as well as 5% for modulus of elasticity were obtained when polymer concrete is irradiated.